If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9xy = 6x + 7 Reorder the terms: 9xy = 7 + 6x Solving 9xy = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6x + 9xy = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -6x + 9xy = 7 + 0 -6x + 9xy = 7 Reorder the terms: -7 + -6x + 9xy = 7 + -7 Combine like terms: 7 + -7 = 0 -7 + -6x + 9xy = 0 The solution to this equation could not be determined.
| (30x+45)=(60x-45) | | 6y=+11 | | 5=3a-3a+2 | | 9x-12=6x-15 | | -5g-4=1 | | 17x-5a-3x-4a= | | 4x+12=-9x-20 | | 55.53+x=95.44 | | -16-3k=6k-5k | | 9x-12=ax-b | | 90x^2-46x+180=0 | | 100-f=60 | | x-18=2/3 | | 4x+12=4x-20 | | 2c-5=-c+5 | | axoverc-b=coverb | | (21x^2-147x+210)=0 | | (8-5i)-(-3-7i)=0 | | 6-2n=6-2n | | 90+x=7x | | 14r-17=39 | | [t+5]+3=-12 | | w-200=100 | | 2y+14=24 | | 4(x+5)=4(x+14) | | .03x+.04(2000+x)=920 | | 15-3r=-6 | | -10x^3-45x^2+45x-30=0 | | 8-4x=2x-9 | | 7cos(2x)=6 | | -x+3=4x-17 | | 8x-7y=32 |